Euler Polynomials and Bi-univalent Functions (European Journal of Pure and Applied Mathematics, 2024)
Our research introduces new subclasses of analytical functions that are defined by Euler polynomials. We then proceed to estimate the Fekete-Szego functional problem and the Maclaurin coefficients for this specific subfamily, denoted as |a2| and |a3|. Furthermore, we demonstrate several new results that emerge when we specialize the parameters used in our main findings.
Keywords: Analytic functions; Bi-univalent functions; Euler polynomials; Fekete-Szeg¨o problem